Marketing training at the arts padepokan in order to develop an arts educational tourism destination - Wuryan Andayani; Diyah Sukanti Cahyaningsih; Ana Sofia Aryati; Retna Safriliana; Prihat Assih; Anorti Ika Wijaya; Purweni Widhianingrum; Silvi Asna Prestianawati (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2024)
The community service team conducted a mentoring program at the Asmoro Bangun Mask Arts Center in the Pakisaji District of Malang City, focusing on marketing management. The Arts Center as a tourist destination will be more widely known and capable of increasing the number of visits if its marketing is handled properly. This marketing mentoring emphasizes the completeness of a tourist destination, including the existence of promotional media that contains important and interesting information about this destination. In order to reach the target market, this mentoring begins with a study of the problems faced by the art center related to marketing. Market surveys are then conducted to map potential markets. From the results of these surveys, brochures are prepared as promotional media. In addition, the servants also provide insights and mentoring so that the group managing the art center has the skills to promote through social media using promotional materials directed by the servant team. In terms of products, namely facilities, and activities, the servants provide input on the arrangement of activities that can attract tourists from their arrival to their departure from this art center. This service is carried out within one semester, and its impact is measured by gathering responses from schools that have received brochures and proposals through the schools' official email. The results show that 40% of the schools that received emails responded positively and showed a significant interest in visiting this art center.